Moscow Population Before and After the COVID-19 Pandemic - A. A. Savina; E. V. Zemlyanova (Здоровье мегаполиса, 2024)
Background. Moscow managed to overcome the challenges of the COVID-19 pandemic by increasing the efforts of the healthcare system and maintaining the birth rate. As a result, the population growth in Moscow remained steady. Like any metropolis, Moscow faces the issue of an aging population, largely due to increased life expectancy, which presents significant challenges for sustainable societal development.Objective. To evaluate the size, composition, and structure of the Moscow population before and after the COVID-19 pandemic.Materials and methods. The authors used the official population data from the Federal State Statistics Service of the Russian Federation (ROSSTAT) and demographic information from the Moscow and Moscow Oblast offices of ROSSTAT (MOSSTAT), focusing on age and gender distributions across municipal areas. The results were visually represented using cartographic tools from the Integrated Data Warehouse of the Information and Analytical System for Comprehensive Development Monitoring in Moscow.Results. In 2021, Moscow's population experienced a decline primarily due to the significant negative effects of the COVID-19 pandemic. However, the number of residents began to increase again afterward. The Moscow population reduced only in 2021 due to the tremendous, negative impact of the COVID-19 pandemic, then the growth in the number of residents recovered. The analysis of the Moscow population pyramid demonstrated a substantial shift towards the older generations. On average, the population of Moscow is two years older than that of the Russian Federation as a whole.Discussion. The demographic landscape of Moscow underwent substantial changes during the pandemic due to complex dynamics in demographic processes. High rates of morbidity and mortality from COVID-19 led to a temporary decrease in the Moscow population and altered natural population movement indicators.Conclusion. Studying the impact of the COVID-19 pandemic on the population size and structure helps to forecast long-term consequences for health and the demographic situation in Moscow. This understanding is essential for developing the relevant improvement programs.